Sous influences : construction et fragilisation de la sensibilité environnementale des habitants des barrios à Santo Domingo - Darysleida Sosa Valdez (Développement Durable et Territoires)
Considered to have no ecological awareness, the inhabitants of the barrios are accused of harming the urban ecosystem. In this sense, two solutions have often been provided: on the one hand, urban interventions mobilize a hygienic and sanitary approach to limit nuisances, and on the other hand, associative actors do not hesitate to impose pre-existing ideologies to promote specific practices. With a perspective of empirical data collected in the field in four Dominican barrios, this article shows how certain inhabitant actions are part of environmental justice and eco-development approaches. At the same time, we show that inhabitants answer to a system of influences that contributes to a dominant and normative construction of environmental awareness.